MENINGKATKANKETERAMPILAN BERMAIN PERAN MELALUI METODE ROLEPLAYING MATERI MEMERANKAN TOKOH DRAMAPENDEK - Maria Friska Nainggolan; Erni Sitompul (Fakultas Ilmu Pendidikan Universitas Sari Mutiara Indonesia, 2019)
This study uses a classroom action research using role playing method. This study aims to improve student skills Role Play. The research instrument used was the performance evaluation sheet, student activity observation sheet and teacher activity observation sheet. The results of this study indicate that the role playing l method can improve students' role playing skills.In the pre-cycle stage the percentage of students completeness was 12.5%, increased in the first cycle to 66.67% and in the second cycle increased to 91.67% and the results obtained by the teacher's activities in the first cycle reached 70% and the second cycle reached 88.75%. And the results obtained for student activity in the first cycle reached 70% and the second cycle reached 82.5%, and reached 75% in the second cycle with an average value reaching 77.5.